(untitled) (LEARNing Landscapes, 2012)
Through this scholarly personal narrative, the author offers insight into how student creativity can be engaged or neglected. While the narrative highlights the potential conflict between students’ lives and their schools, the hope lies in the illuminative power of stories of difficulty. By interweaving narrative and theory, the author sheds light on the conditions that inhibit creativity, and emphasizes the capacity of teachers to locate creative, compassionate spaces for themselves and their students.